2023
DOI: 10.3389/fcvm.2023.1202381
|View full text |Cite
|
Sign up to set email alerts
|

Application of next generation sequencing in cardiology: current and future precision medicine implications

Abstract: Inherited cardiovascular diseases are highly heterogeneous conditions with multiple genetic loci involved. The application of advanced molecular tools, such as Next Generation Sequencing, has facilitated the genetic analysis of these disorders. Accurate analysis and variant identification are required to maximize the quality of the sequencing data. Therefore, the application of NGS for clinical purposes should be limited to laboratories with a high level of technological expertise and resources. In addition, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 165 publications
0
3
0
Order By: Relevance
“… 50 In RCM, TTE findings of diastolic dysfunction with atrial enlargement could be observed, but cardiac magnetic resonance could be of greater diagnostic value with high specificity to differentiate from other mimics, such as constrictive pericarditis. 51 52 …”
Section: The Role Of Genetic Testing In Risk Stratification Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“… 50 In RCM, TTE findings of diastolic dysfunction with atrial enlargement could be observed, but cardiac magnetic resonance could be of greater diagnostic value with high specificity to differentiate from other mimics, such as constrictive pericarditis. 51 52 …”
Section: The Role Of Genetic Testing In Risk Stratification Strategiesmentioning
confidence: 99%
“…Patients with these variants are often associated with debilitating outcomes, requiring implantable cardiac defibrillators to prevent sudden cardiac death. 52 Yet, almost 55% of pathogenic variants in DCM are idiopathic and may overlap with variants causing ACM, highlighting the need to implement better classification in a genotypic setting. 55 …”
Section: The Role Of Genetic Testing In Risk Stratification Strategiesmentioning
confidence: 99%
“…This approach offers the potential for more effective and personalized treatments and improved patient outcomes ( 11 ). The primary advantage of targeted therapies is their precision in addressing the root causes of the diseases ( 16 ). Instead of relying solely on broad-spectrum medications, these therapies can pinpoint specific molecular pathways, proteins, and cellular processes involved in disease pathogenesis ( 17 ).…”
Section: Introductionmentioning
confidence: 99%